Letters from the Voyages of the Slave Ship Pearl - Diptee, Audra A. (Ian Randle Publishers, 2018)
"The barbarity of the enforced migration of Africans to the Caribbean and the realities of the transatlantic slave trade are fully revealed in Letters from the Voyages of the Slave Ship PEARL. The nonchalant accounts of the awful details of suffering and death are brought into sharp relief by the editors who reconstruct four voyages of the PEARL between 1785 and 1793. The ship was owned by Bristol businessman James Rogers, and the letters in this collection are but a small sample of the 15 boxes of correspondence comprising the Rogers papers held at The National Archives at Kew in the United Kingdom. Caribbean scholars who can scarcely access the original records are provided with a closer understanding of the complexities of slave trading. Written from several perspectives - the ship's doctor, the captains, slave traders on the African coast and Caribbean merchants - this assemblage offers a unique glimpse into the transatlantic slave trade. The letters, however, do not cover the perspective of the enslaved - muted and reduced to cargo, mentioned and recorded by number only. The book is divided into four parts for each of the selected voyages and each part is introduced with a short synopsis, each letter elucidated with explanatory notes. The work is enhanced by the inclusion of maps, tables and figures. Letters from the Voyages of the Slave Ship PEARL contextualises the continuing conversation of a painful past and is both enlightening and informative for the scholar, activist, and advocate alike."--Page 4 of cover.